A case of ruptured mucinous cystadenoma of the pancreas with recurrence-free survival for 8 years - Atsuro Fujinaga; Teijiro Hirashita; Yukio Iwashita; Hiroaki Nakanuma; Kazuhiro Tada; Takashi Masuda; Yuichi Endo; Masayuki Ohta; Hideki Ono; Kazunari Murakami; Masafumi Inomata (Surgical Case Reports)
Abstract Background Pancreatic mucinous cystic neoplasm (MCM) presenting with rupture is extremely rare, and very few studies have followed up patients over the long term after ruptured mucinous cystadenoma (MCA). We report a case of ruptured MCA of the pancreas with recurrence-free survival for 8 years. Case presentation A 28-year-old Japanese woman was admitted to the emergency department of a local hospital after experiencing acute abdominal pain. Abdominal computed tomography revealed massive ascites and the presence of a cystic tumor measuring 60 mm in diameter in the pancreatic tail. Conservative therapy with antibiotics and abdominal drainage were performed to treat peritonitis that occurred secondary to the ruptured pancreatic cystic tumor, after which the patient’s symptoms improved. The patient was referred to our department for further examination and treatment. We diagnosed a ruptured MCN and performed laparoscopic spleen-preserving distal pancreatectomy. Histopathological findings revealed ovarian-type stroma, which tested positive for estrogen and progesterone receptors by immunohistochemistry. The histopathological diagnosis was MCA. The postoperative course was uneventful, and the patient remains alive without any evidence of recurrence at 8 years postoperatively. Conclusion A good prognosis is possible even in cases of ruptured MCA. Because of the risk of peritoneal dissemination after ruptured MCA, long-term follow-up is important.